The Functional Organization and Cortical Connections of Motor Cortex in Squirrels - Cooke, Dylan F. (Oxford University Press, 2012)
Despite extraordinary diversity in the rodent order, studies of motor cortex have been limited to only 2 species, rats and mice. Here, we examine the topographic organization of motor cortex in the Eastern gray squirrel (Sciurus carolinensis) and cortical connections of motor cortex in the California ground squirrel (Spermophilus beecheyi). We distinguish a primary motor area, M1, based on intracortical microstimulation (ICMS), myeloarchitecture, and patterns of connectivity. A sensorimotor area between M1 and the primary somatosensory area, S1, was also distinguished based on connections, functional organization, and myeloarchitecture. We term this field 3a based on similarities with area 3a in nonrodent mammals. Movements are evoked with ICMS in both M1 and 3a in a roughly somatotopic pattern. Connections of 3a and M1 are distinct and suggest the presence of a third far rostral field, termed “F,” possibly involved in motor processing based on its connections. We hypothesize that 3a is homologous to the dysgranular zone (DZ) in S1 of rats and mice. Our results demonstrate that squirrels have both similar and unique features of M1 organization compared with those described in rats and mice, and that changes in 3a/DZ borders appear to have occurred in both lineages.